2023
DOI: 10.7554/elife.81701
|View full text |Cite
|
Sign up to set email alerts
|

Object representation in a gravitational reference frame

Abstract: When your head tilts laterally, as in sports, reaching, and resting, your eyes counterrotate less than 20%, and thus eye images rotate, over a total range of about 180°. Yet, the world appears stable and vision remains normal. We discovered a neural strategy for rotational stability in anterior inferotemporal cortex (IT), the final stage of object vision in primates. We measured object orientation tuning of IT neurons in macaque monkeys tilted +25 and –25° laterally, producing ~40° difference in retinal image … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Also, in non-human primates, neural activity in response to visual inputs in the lower visual cortex, including V1 (Horn et al, 1972;Tomko et al, 1981) and V2/3 (Sauvan and Peterhans, 1999), is found to be affected by the direction of gravity. Furthermore, higher association areas such as the caudal intraparietal area (Rosenberg and Angelaki, 2014) and inferotemporal cortex (Emonds et al, 2023) have been found to visually encode the tilt orientation of an object with respect to the gravitational vertical. When combining the present results with previous neurophysiological findings, it is possible to speculate that orientation information about visual objects might be integrated with vestibular-derived gravitational information at multiple stages of bottom-up visual processing, including the MOG.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in non-human primates, neural activity in response to visual inputs in the lower visual cortex, including V1 (Horn et al, 1972;Tomko et al, 1981) and V2/3 (Sauvan and Peterhans, 1999), is found to be affected by the direction of gravity. Furthermore, higher association areas such as the caudal intraparietal area (Rosenberg and Angelaki, 2014) and inferotemporal cortex (Emonds et al, 2023) have been found to visually encode the tilt orientation of an object with respect to the gravitational vertical. When combining the present results with previous neurophysiological findings, it is possible to speculate that orientation information about visual objects might be integrated with vestibular-derived gravitational information at multiple stages of bottom-up visual processing, including the MOG.…”
Section: Discussionmentioning
confidence: 99%